2005
DOI: 10.1097/01.mao.0000169046.31136.1a
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Helicobacter pylori in the Etiopathogenesis of Chronic Otitis Media

Abstract: Even though it is possible to detect Helicobacter pylori in middle ear cleft in chronic otitis media, its role in the etiopathogenesis of the issue is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…16 Initially, the human stomach was thought to be the only H pylori reservoir, until the bacterium was discovered in human dental plaque, oral lesions, saliva and faeces. 4, 6 In the literature, gastroesophageal reflux has been suggested as an inflammatory cofactor and a possible cause for most adult and paediatric upper respiratory tract disorders. 13,17 Some studies have suggested gastroesophageal reflux as an aetiological factor in otitis media with effusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Initially, the human stomach was thought to be the only H pylori reservoir, until the bacterium was discovered in human dental plaque, oral lesions, saliva and faeces. 4, 6 In the literature, gastroesophageal reflux has been suggested as an inflammatory cofactor and a possible cause for most adult and paediatric upper respiratory tract disorders. 13,17 Some studies have suggested gastroesophageal reflux as an aetiological factor in otitis media with effusion.…”
Section: Discussionmentioning
confidence: 99%
“…20 There are also studies suggesting H pylori in the aetiology of chronic otitis media. 6,7 The CLO test is supplied as a kit, and detects the urease enzyme of H pylori. The test has a high sensitivity and specificity for H pylori detection; one study found a specificity of 97 per cent and a sensitivity of 98 per cent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This test, however, may have poor specificity for detecting H. pylori organisms in extragastric areas; it has been shown to yield high false-positive rates in both adenoid and ear effusion samples [37]. In recent case series that used PCR, H. pylori genetic material was rarely detected in adenoid tissue samples [37][38][39], whereas it was detected in middle ear samples with widely varied frequency, ranging from 8% to 67% of children examined [39][40][41]; children with bilateral OME often had H. pylori organisms detected in one ear but not the other. In two case series, investigators attempted to culture H. pylori organisms from adenoid tissue or middle ear effusion samples with negative results [38,42].…”
Section: Chronic Otitis Mediamentioning
confidence: 95%
“…The authors hypothesized a causative link between H. pylori infection and anterior uveitis, though the small sample size makes this conclusion tentative [21]. The presence of H. pylori in middle ear effusion of patients with otitis media has been reported by three recent studies [23][24][25]. The presence of H. pylori in middle ear effusion of patients with otitis media has been reported by three recent studies [23][24][25].…”
Section: Head and Neck Diseasesmentioning
confidence: 99%